Improved Oxidation Stability of Camellia Oil-in-Water Emulsions Stabilized by the Mixed Monolayer of Soy Protein Isolate/Bamboo Shoot Protein Complexes - Yuhang Xi (Frontiers Media S.A., 2021)
The complex of soy protein isolate (SPI)/bamboo shoot protein concentrate (BPC) was developed to stabilize camellia oil-in-water (O/W) emulsions. The surface hydrophobicity of the BPC/SPI complex driven by hydrogen bonds and electrostatic attractions was improved. With the increasing ratio of BPC in the complex, a tighter network layer structure of the complex was formed due to the rearrangement of proteins, and the emulsions showed a progressive enhancement in the gel-like structures. At the SPI/BPC ratio of 2:1, the emulsions had smaller droplet size and lower creaming index of 230 nm and 30%, and the emulsifying activity and stability indices of the emulsions were 803.72 min and 11.85 g/m2, respectively, indicating a better emulsifying activity and stability of emulsions. Meanwhile, the emulsions stabilized by the complex at the ratio of 2:1 showed better storage and antioxidant stability. These findings are expected to develop the application of bamboo shoots in emulsion-based food products such as mayonnaise, salad dressings, and sauces.